Leadership Strategies of Madrasah Heads in Improving Teachers' Professional Competence at Man 1 Aceh Tenggara - Nur Azizah; Yusuf Hadijaya; Neliwati (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research was conducted because of the lack of professional competence of teachers in performing their duties. This is supported by the following phenomena, namely there are teachers who lack knowledge in teaching the material taught, there are teachers who do not understand the psychology of students so that the material taught does not touch (need assessment) the needs of students. The research methodology used is a qualitative research design by applying a phenomenological approach. The data collection techniques that researchers use are interviews, observations and documentation studies. The primary data sources in this study are the madrasah head and teachers, while secondary data comes from school stakeholders including parents and students. The analysis method used in this research is qualitative analysis. The results of this study indicate that the madrasah head at MAN 1 Aceh Tenggara plays an important role in three main aspects: communication, curriculum development, and administration. The madrasah head at MAN 1 Aceh Tenggara can improve teacher competence with effective leadership strategies as a supervisor. This includes setting standards, regular monitoring and feedback, evaluating performance, as well as providing training, mentoring, and collaboration among teachers The madrasah principals at MAN 1 Aceh Tenggara play a crucial role as managers in improving teachers' competencies. Effective coordination, performance monitoring and professional development are key to recognising teachers' achievements and helping to strengthen commitment to the school's vision, encouraging innovation in an increasingly complex education landscape. Teachers' professional competence at MAN 1 Aceh Tenggara district is key to creating effective and engaging learning.